O valor de mercado da educaç\~ao pública - Sergei Suarez Dillon Soares (Instituto de Pesquisa Econômica Aplicada (IPEA), 2017)
– This article estimates the market value of public education by comparing standardized test scores of students in public and private schools. The idea is to assign to the education of each public school student a market value equivalent to the tuition paid by private school students with similar test score results. The implementation requires an expenditure survey, or other database to provide information on tuitions, and standardized test scores available for both private and public schools. This article uses Brazilian test score data, which are particularly good. The main results are not surprising. Pre-school, primary, and secondary education are all highly progressive government transfers. Furthermore, since their market value is superior to public expenditures in each of these educational levels, they are also welfare enhancing. The flip side is that public higher education is both highly regressive and welfare reducing.
Keywords: I24; 330; public education; value of education; educational proficiency